Development and Validity of Fluid Intelligence Test Based on Cattle-Horn-Carrol Theory: A Pilot Project - Fitri Andriani; Cholichul Hadi; Pramesti Pradna Paramita (INSAN Jurnal Psikologi dan Kesehatan Mental, 2016)
This study aimed to examine the validity of the Fluid Intelligence Test, constructed based on the Cattel-Horn-Carroll theory. There were two sources of validity used in this study, which were evidence based on the internal structure and evidence based on relation with other variables. Sixty-four items have been composed and tested to 242 people. The data was analyzed using confirmatory factor analysis technique and correlations technique to examine test validity. The result of this study showed that the prepared model worked quite well in describing the narrow abilities of fluid intelligence, as showed by the receipt of fit indexes accuracy of the model, such as Chi-Square value .42 (p = .518), Goodness Fit Index (GFI) = 1, and Rooted Mean Square Error (RMSEA) = .00. Similar result was also showed by its correlation with other variables, which are .717 (TIKI) and .606 (CFIT). This suggested that Fluid Intelligence Test has good validity.